Analysis of Students' Conceptual Understanding of Physics on the Topic of Static Fluids - Jamaludin Jamaludin; John Rafafy Batlolona (Jurnal Penelitian Pendidikan IPA, 2021)
Physics misunderstandings still occur in high school students now. Therefore, it requires complete learning so that students' conceptual physics can be stable and embedded in everyone. This study aimed to diagnose the extent to which students' conceptual understanding of physics on the topic of static fluid is. This study used a survey approach to form a written test for 100 senior high schools in two schools in Central Maluku Regency. The results showed that there were still many students who experienced fluid misconceptions in cases 2, 3, and 5 to achieve a good level. Therefore, deep learning is needed so that students' conceptual physics will be good and not forgotten